Visitors’ use of information kiosk at Melaka town heritage sites / Mohd Hasrul Yushairi Johari ... [et al.] - Johari, Mohd Hasrul Yushairi; Mat Roni, Mohd Saiyidi Mokhtar; Ahmad, Amiruddin; Md. Hasim, Ahmad Khairuman (Institute of Business Excellence and UPENA, 2010)
The advancement in information and communication technology (ICT) has garnered much interest in various fields. Tourism arena is one of the many fields in which ICT has become a subject of interest. Although in the late 90’s and in the early 21st century virtual tourism was predicted to have a major impact, traditional visit to places of attraction still remains popular. Therefore, the visitor’s appreciation and knowledge on certain places of attraction may improve through an integration of virtual tourism into a conventional physical movement. This will later could help induce further interest to visit. This integration can take in many forms. One of the many significant approaches to this method is to deploy an ICT based information kiosk. Adapting the intrinsic value of information through the information kiosk however, requires more than just the technology. Social norms and user behaviour has to be adequately studied in order to better understand the visitors intention and likelihood to use such technology. Perhaps, the deployment of such technology is viewed as a catalyst to lure interest among visitors to heritage sites. Therefore, understanding the social behaviour among visitors would contribute useful information on the technical aspects of the kiosk such as design, concept and content. Several theories of social behaviour are studied and the most applicable theory is used to explain the intention and the actual use of the kiosk. Derived from the Theory of Reasoned Action which is later refined into Theory of Planned Behaviour, a model called Unified Theory of Acceptance and Use of Technology (UTAUT) is adapted in this study. The use of UTAUT is considered appropriate in current study as it incorporates several parameters that help to explain the use of an ICT based information kiosk among visitors.